Optimization of the dipeptide motifs in the PSMA ligands linker structure: synthesis and in vitro evaluation - Uspenskaya, Anastasiia A.; Nimenko, Ekaterina A.; Shafikov, Radik R.; Zyk, Nikolay Y.; Evteev, Sergei A.; Dashkova, Natalia S.; Ivanenkov, Yan A.; Majouga, Alexander G.; Skvortsov, Dmitry A.; Garanina, Anastasiia S.; Beloglazkina, Elena K.; Machulkin, Aleksei E. (Medicinal chemistry research, 2023)
An improved series of ligands targeting prostatic specific membrane antigen has been reported. Varying compounds and their biological parameters were due to changes in the linker structure. Highly selective compounds with nanomolar IC 50 values were obtained. As an example, a conjugate with Sulfo-Cy5 and MMAE was obtained and pre-studied. Graphical Abstract